Aplikasi LIKU (Literasi Keuangan) Berbasis Android untuk Meningkatkan Financial Literacy Pelaku UMKM - Mardiani, Novita; Juwita, Kristin (SAFE-Network, 2024)
This research aims to measure LIKU financial application can improve financial literacy and help Micro, Small Medium Enterprise (MSMEs) run their business with the ease of digital bookkeeping. The research method is used descriptive analysis using primary data sources in the form of questionnaires distributed to 60 respondents who are MSMEs in Jombang and have fulfilled several criteria set by the researcher. The research results show that MSMEs need financial applications that prioritize: general experience and needs, financial application features and functions, ease of use, security and privacy, cost and accessibility. The LIKU financial application is a financial application that is easy to use, has security and privacy, has easy access because it uses an Android-based cell phone, and is affordable because MSMEs only need to use internet data to access the application. The LIKU application can also increase insight into financial literacy to avoid business fraud for MSMEs in Jombang Regency.